PENGARUH TEKANAN UDARA PADA KOMPOR BENSIN TERHADAP PRESTASI PEMBAKARAN DENGAN METODE PENGUAPAN - Bayu Maidi Alkarim; Raden Hengki Rahmanto; M Irham Mahfud (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2018)
Vapor carburetor was invented by Tom Ogle in 1971. By his invention, fuel consumption of vehicle more economic than conventional carburetor. In the rare and high price of LPG, writer made a machine which has same principle with vapor carburetor. Gasoline stove can be an alternative and solution for many problem caused gas stove. Writer used aerator as an air supplier and also as vaporizer of pertalite. Writer compared Specific Fuel Consumption (SFC) every pressure (variable) which is as an indicator of combustion performance. According from this experiment showed smallest SFC number was happened on 0,6 kPa, which at this point was happened optimum combustion. Generally, at pressure range 0,6 kPa to 2,5 kPa, higher pressure will increase Specific Fuel Consumption (SFC) number, but the other way will need shorter time.